KUALITAS LAYANAN PORTAL OPEN DATA BANDA ACEH (ODBA) DALAM KETERBUKAAN INFORMASI PUBLIK DI DINAS KOMUNIKASI INFORMATIKA DAN STATISTIK KOTA BANDA ACEH - Atthariq Naufal Athallah (Jurnal Teknologi dan Komunikasi Pemerintahan, 2022)
One of the goals of the reform program in Indonesia is the realization of good governance. The Indonesian Open Government Movement (OGI) is a form of movement between the government and the community to realize good governance, namely through principles based on public information. One of the OGI programs to achieve this is through the open data project portal, one of which is the Banda Aceh Open Data Portal (ODBA). This study aims to find out how the quality of ODBA Portal services in public information at the Department of Communication, Informatics and Statistics (Diskominfontik) of Banda Aceh City and the strategy of Banda Aceh Diskominfotik to improve the quality of ODBA Portal services. The research method used is descriptive qualitative. Informants in this study were determined by purposive sampling technique. Data were collected by interview, observation, documentation, and triangulation techniques. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The theory used is based on three dimensions of the quality of a portal site proposed by Rocha (2012: 374-382), namely content quality, service quality, and technical quality. The results showed that the service quality of the ODBA Portal was quite good. However, there are several things that need to be improved on the ODBA Portal, such as the availability of features for proposing datasets, features for feedback, special personnel to handle open data portal maintenance, and others. To make the ODBA Portal have a better quality, the Department of Communication, Informatics and Statistics of Banda Aceh City needs to provide expert programmers, especially in the field of maintenance and add the main features that must exist in an open data portal. The City of Banda Aceh Diskominfotik has also implemented several strategies to improve the quality of the ODBA Portal service. Keywords: ODBA Portal, Open Data, Open Data Portal, Public Information Disclosure, Quality of Website Portal